2025 Western Kansas Agricultural Research Report (Kansas Agricultural Experiment Station Research Reports, 2025)
Summary of research conducted in 2024-2025 and prior years on field production and management practices for crops in western Kansas. Published in 2025 from the Kansas State University Agricultural Experiment Station and Cooperative Extension Service.
Keywords: crops; tillage; irrigation; weeds